Early weight gain after stopping smoking: a predictor of overall large weight gain? A single-site retrospective cohort study - Pankova, Alexandra; Kralikova, Eva; Zvolska, Kamila; Stepankova, Lenka; Blaha, Milan; Ovesna, Petra; Aveyard, Paul (BMJ open, 2018)
OBJECTIVES: Most people gain weight on stopping smoking but the extent of weight gain varies greatly. Interventions aimed at all quitters to prevent weight gain on cessation have proven unpopular but targeting people who have gained excess weight immediately after quitting may improve uptake and cost-effectiveness. We examined whether early large postcessation weight gain predicts overall large weight gain. DESIGN: Retrospective cohort study. SETTING: Primary care setting-smoking cessation centre in Prague, Czech Republic. PARTICIPANTS: Out of 3537 patients treated between 2005 and 2013, 1050 were continuous abstainers (verified by carbon monoxide measurement) at 1-year follow-up and formed the cohort of the current report. 48.7% were women (n=511) with the mean age of 46 (±14.4) years. METHODS: In this retrospective cohort study, all patients underwent usual tobacco dependence treatment using evidence-based methods. Weight was measured prior to smoking cessation and at each visit after quitting. RESULTS: The mean weight gain in the first month (n=763) was 0.79% (±2.03%), in the second month (n=646) was 1.49% (±2.58%), for the third month (n=566) 2.33% (±3.44%) and 4.1% (±5.31%) after 1-year follow-up (n=1050). The regression coefficient per 1% rise in the first 3 months was +0.13% (95% CI -0.04% to 0.30%). A receiver operating curve analysis showed that patients gaining more than 0.98% of their baseline weight during first 3 months had a sensitivity of 66% and specificity of 44% for gaining 7% or more weight by 12 months. In addition, lower body mass index and an increase in appetite at 3 months after quitting were associated with greater weight gain, while using nicotine replacement therapy was associated with less weight gain at 1-year follow-up. CONCLUSIONS: People who stop smoking and gain a larger amount of weight early after quitting are not more likely to gain excessively at 1 year.
Keywords: index tělesné hmotnosti; Weight Gain; kouření; body weight changes; Retrospective Studies; Prognosis; lidé; Česká republika; Middle Aged; mužské pohlaví; smoking cessation; Smoking Cessation Agents; Adult; Overweight; smoking; Czech Republic; Body Mass Index; hmotnostní přírůstek; Appetite; Smoking Cessation; Smoking; nikotin; ženské pohlaví; prognóza; retrospektivní studie; Humans; chuť k jídlu; lidé středního věku; weight; nadváha; weight gain; dospělí; Female; Nicotine; odvykání kouření; látky pro odvykání kouření; Male